2017
DOI: 10.1097/ta.0000000000001358
|View full text |Cite
|
Sign up to set email alerts
|

Severe injuries associated with skiing and snowboarding

Abstract: Prognostic/epidemiologic, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 33 publications
3
54
0
Order By: Relevance
“…Not unexpectantly, older boys are mostly involved in winter sport accidents . We found that patterns of injury are consistent with data from other studies, with the predominance of head trauma in severe snow sport injuries . Thanks to strong prevention campaigns established in the last 10 years, the helmet is more widely used in our cohort compared to older studies .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Not unexpectantly, older boys are mostly involved in winter sport accidents . We found that patterns of injury are consistent with data from other studies, with the predominance of head trauma in severe snow sport injuries . Thanks to strong prevention campaigns established in the last 10 years, the helmet is more widely used in our cohort compared to older studies .…”
Section: Discussionsupporting
confidence: 89%
“…Thanks to strong prevention campaigns established in the last 10 years, the helmet is more widely used in our cohort compared to older studies . Interestingly, the proportion of people wearing helmets is lower in the adult population …”
Section: Discussionmentioning
confidence: 95%
“…Except for cross-country skiing, trauma-related deaths are prevalent in all winter mountain sports activities that have been addressed. The main preventive measure to reduce traumatic deaths is the use of protective gear like helmets [61,62]. The helmet rate is already above 90% in alpine skiing [63], but still low in other winter sports (e.g., 50% and below in sledging [60]).…”
Section: Discussionmentioning
confidence: 99%
“…The helmet rate is already above 90% in alpine skiing [63], but still low in other winter sports (e.g., 50% and below in sledging [60]). In addition to sledging, helmet use should be especially promoted in snowboarders younger than 30 years and older than 60 years of age [62]. Further preventive measures include increased awareness of potential risk factors, e.g., fall and collision hazards, avalanche danger, and freezing and hypothermia risk, and the selection of a downhill skiing and sledging velocity appropriate to the individual skill level [5,23].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have reported that the cases of skiing injuries have increased. Moreover, these studies have shown that skiing injuries have mostly occurred for recreational alpine skiing and snowboard among children, adolescents, and adults [4,5]. Many people who participate in recreational skiing and snowboard every year suffer severe sportsrelated injuries such as: sprains, fractures contusions, lacerations, dislocations, and concussion [6].…”
Section: Introductionmentioning
confidence: 99%